Selection Of Educative Play Equipment For Teacher TK/PAUD ABA III Rewwin, Waru, Sidoarjo - Siti Rahayu Nasichatu Muslimatin; Defi Fefdianti (Shof Journal of Social Impact, 2024)
Based on the explanation above, it can be concluded that the dissemination of guidelines for selecting educational game equipment for teachers of Kindergarten/PAUD ABA III Rewwin, Waru, Sidoarjo is very useful and helps in enriching knowledge about selecting game equipment for students. For the purchase and manufacture of educational play equipment, teachers will then pay attention to suitability to the needs of children's growth and development. This is done so that children's growth and development can develop optimally through these educational game tools. There are examples of educational game tools, such as APE from used cardboard, rags, foam and sponges, etc.